Immunization with Irradiated Tumour Cells and Specific Lymphocyte Cytotoxicity in Malignant Melanoma. Issue 5757 (8th May 1971) - Currie, G. A.; Lejeune, F.; Fairley, G. Hamilton
Abstract : A microculture technique has been adapted to assay the cytotoxic properties of the lymphocytes from patients with malignant melanoma when cultured with their autologous tumour cells. In a series of patients with established melanoma specific autologous cytotoxicity was extremely uncommon, being detectable in only 3 out of the 22 cases studied. This cytotoxicity did not correlate with clinical staging of the disease but may well have been related to tumour volume. By autoimmunization of patients with an irradiated suspension of their own tumour cells the appearance of cytotoxic lymphocytes could be provoked in 5 out of the 12 patients studied. This cytotoxicity was detectable at the end of the first week after the autograft and disappeared by the third week. Cytotoxic lymphocytes did not correlate in any obvious way with the appearance of specific antitumour antibodies detected by immunofluorescence. So far there has been no evidence of a serum factor capable of blocking the lymphocyte cytotoxicity in these patients. The presence and possible significance of cytotoxic lymphocytes in patients with malignant disease is discussed.